Traffic Congestion and Congestion Pricing - C. Robin Lindsey; Erik T. Verhoef (Tinbergen Institute, 2000)
For several decades growth of traffic volumes has outstrippedinvestments inroad infrastructure. The result has been a relentless increase intrafficcongestion. This paper reviews the economic principles behindcongestionpricing in static and dynamic settings, which derive from thebenefits ofcharging travellers for the externalities they create. Specialattention ispaid to various complications that make simple textbook congestionpricingmodels of limited relevance, and dictate that congestion pricingschemes bestudied from the perspective of the theory of the second best. Thesecomplications include pricing in networks, heterogeneity of users,stochasticcongestion, interactions of the transport sector with the rest of theeconomy,and tolling on private roads. Also the implications of congestionpricing foroptimal road capacity are considered, and finally some explanationsfor thelongstanding social and political resistance to road pricing areoffered.
Keywords: 330; Verkehrsstau; Straßenbenutzungsgebühr; Theorie